A Taxonomy of Accountable Care Organizations for Policy and Practice. (23rd September 2014) - Shortell, Stephen M.; Wu, Frances M.; Lewis, Valerie A.; Colla, Carrie H.; Fisher, Elliott S.
<x xml:space="preserve">Abstract</x> Objective To develop an exploratory taxonomy of Accountable Care Organizations (ACOs) to describe and understand early ACO development and to provide a basis for technical assistance and future evaluation of performance. Data Sources/Study Setting Data from the National Survey of Accountable Care Organizations, fielded between October 2012 and May 2013, of 173 Medicare, Medicaid, and commercial payer ACOs. Study Design Drawing on resource dependence and institutional theory, we develop measures of eight attributes of ACOs such as size, scope of services offered, and the use of performance accountability mechanisms. Data are analyzed using a two‐step cluster analysis approach that accounts for both continuous and categorical data. Principal Findings We identified a reliable and internally valid three‐cluster solution: larger, integrated systems that offer a broad scope of services and frequently include one or more postacute facilities; smaller, physician‐led practices, centered in primary care, and that possess a relatively high degree of physician performance management; and moderately sized, joint hospital–physician and coalition‐led groups that offer a moderately broad scope of services with some involvement of postacute facilities. Conclusions ACOs can be characterized into three distinct clusters. The taxonomy provides a framework for assessing performance, for targeting technical assistance, and for diagnosing potential antitrust violations.